2018
DOI: 10.1037/bdb0000061
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking cross-cultural adaptability using behavioral developmental theory: An analysis of different migrant behaviors.

Abstract: The rate of international migration has reached unprecedented levels over the past few decades (Schwartz, Unger, Zamboanga, & Szapocznik, 2010). According to the International Organization for Migration, the number of migrants worldwide was 244 million in 2015. Current literature in cross-cultural adaptability describes acculturation as a 4-phase process, namely honeymoon, crisis, adjustment, and biculturalism (Sawyer, 2012). This approach characterizes all migrants equally, regardless of the type of migrant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…Berada pada kategori sedang culture shock mahasiswa yang berasal dari luar sumatera barat terkait dipicu dari kecemasan yang akan menimbulkan akibat hilangnya tanda dari hubungan sosial yang selama ini dikenal dengan interaksi sosial, seperti petunjuk dalam bentuk kata-kata, ekspresi wajah, isyarat-isyarat, kebiasaan, dan norma yang diperoleh individu dari perjalanan hidupnya mulai dari individu tersebut lahir (Ramakrishnan, Barker, Vervoordt, & Zhang, 2017).…”
Section: Deskripsi Culture Shockunclassified
“…Berada pada kategori sedang culture shock mahasiswa yang berasal dari luar sumatera barat terkait dipicu dari kecemasan yang akan menimbulkan akibat hilangnya tanda dari hubungan sosial yang selama ini dikenal dengan interaksi sosial, seperti petunjuk dalam bentuk kata-kata, ekspresi wajah, isyarat-isyarat, kebiasaan, dan norma yang diperoleh individu dari perjalanan hidupnya mulai dari individu tersebut lahir (Ramakrishnan, Barker, Vervoordt, & Zhang, 2017).…”
Section: Deskripsi Culture Shockunclassified
“…In addition, regardless of job conditions, adaptability resources were positively associated with both general and occupational wellbeing (Maggiori et al, 2013). Other studies have investigated refugees' career adaptability (see Campion, 2018;Ramakrishnan, Barker, Vervoordt, & Zhang, 2018;Wehrle, Kira, & Klehe, 2019). Findings showed that career adaptability plays a crucial role in the resettlement process: it enables the activation of internal resources required to modify expectations and implement adaptive coping strategies to deal with resettlement (Campion, 2018).…”
Section: Career Adaptabilitymentioning
confidence: 99%
“…The relationship between job insecurity, career adaptability, and both general and occupational well-being was investigated, and results showed that, regardless of job conditions, adaptability resources were positively associated with both general and occupational well-being (Maggiori et al 2013;Lodi et al 2020). Other studies have investigated refugees' career adaptability (see Campion 2018;Ramakrishnan et al 2018;Wehrle et al 2019). Findings showed that career adaptability plays a crucial role in the resettlement process by enabling the activation of internal resources required to modify expectations and implement adap-tive coping strategies to deal with resettlement (Campion 2018).…”
Section: Career Adaptabilitymentioning
confidence: 99%